Developing infographic media of physics based on ethnoscience - Wati, Widya (IAIN Palangka Raya, 2024)
This research develops an ethnoscience physics infographic using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model as an innovative solution to support the learning process. This systematic and structured development model aims to produce a valid and practical infographic capable of presenting physics material information accurately in a simple and easily digestible format. The validation process was conducted through expert assessment using validation sheets, while practicality was evaluated through student response questionnaires. Research results showed that the ethnoscience physics infographic achieved a highly valid category, indicating its suitability as a supporting medium for introductory physics lectures. Student responses were highly positive, with high ratings on attractiveness, ease of understanding, and practical usage. The research significantly contributes to developing innovative and effective learning strategies in higher education.